Export of textiles and garments made from recycled PET and cotton to South Korea (2021)
In the framework of the international cooperation between Colombia and South Korea, this study aims to assess the opportunity for Colombian producers of textiles and garments made with PET  and recycled cotton to export to South Korea; Along with the environmental, social, and economic problems experienced by the fashion industry, coupled with the trend of the new generations who prefer responsible consumption and encourage the question that is the basis of this study, a mixed research methodology was used. It was required to work mainly with the analysis of the information collected, such as market data, interviews with producers, and consumer studies. In addition, some recommendations are made to textile producers with a view to exporting to this country, and the behavior of consumers in this market is also studied through literature review and marketing studies.